Quality Protein Maize for Food, Feed and Nutritional Security - Kaul, Jyoti; Kumar, Ramesh; Chaudhary, Dharam Paul (Indian Farming, 2015)
QPM hybrid seed availability is an issue that concerns the public institutions as no private organizations have ventured into QPM research. So, to solve the availability of quality seed, special attention has to be paid by developing regional seed hubs. Such alternative sites for seed production of QPM hybrids may be identified with requisite isolation distance, good connectivity of roads, assured irrigation and storage facilities. Directorate of Maize research (DMR) identified one such location in West Bengal and seed production of HQPM-1 has been taken up at farmers field under seed village mode with the active support and help of a farmer group called Krishi Swambar Gosthi, Kulgachi, Nadia (W.B.) and another site, i.e. Banswada and Dungarpur district of Rajasthan have been identified where Rajasthan State Seed Corporation has taken lead in close association with National Seed Corporation of India (NSC) and DMR. NSC in collaboration with DMR has organized hybrid seed production trainings for farmers in these areas and trained hundreds of farmers.